2016
DOI: 10.18677/enciclopedia_biosfera_2016_057
|View full text |Cite
|
Sign up to set email alerts
|

Fontes E Doses De Nitrogênio No Cultivo Do Milho Safrinha Em Sucessão À Soja

Abstract: RESUMOObjetivando avaliar a influência de fontes e doses de N em cobertura sobre o desempenho do milho safrinha, após a soja, conduziu-se a presente pesquisa em Itiquira -MT, na safrinha de 2014, num Latossolo Vermelho distrófico muito argiloso. Os tratamentos foram dispostos em delineamento de blocos ao acaso, em esquema fatorial incompleto (3x4)+1, sendo: três fontes de N (ureia tradicional, ureia com aditivo e nitrato de amônio), quatro doses de N (30, 60, 90 e 120 kg ha de N via fosfato monoamônico e 1,0 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
3
0
4
Order By: Relevance
“…Characteristic defined in the V8 stage, showing a possible decrease in nitrogen loss and making this element available, resulting in an increase in the number of rows (CARMO et al, 2012). Kappes and Silva (2016) obtained values of average increase of 7.6% in grain productivity with the application of N, in relation to the treatment without application of N in coverage, regardless of the urea used. Kappes et al (2009), observed a significant increase in corn productivity with application of 70 kg ha-1 of N, regardless of the source used.…”
Section: Resultsmentioning
confidence: 79%
“…Characteristic defined in the V8 stage, showing a possible decrease in nitrogen loss and making this element available, resulting in an increase in the number of rows (CARMO et al, 2012). Kappes and Silva (2016) obtained values of average increase of 7.6% in grain productivity with the application of N, in relation to the treatment without application of N in coverage, regardless of the urea used. Kappes et al (2009), observed a significant increase in corn productivity with application of 70 kg ha-1 of N, regardless of the source used.…”
Section: Resultsmentioning
confidence: 79%
“…Some single-crosses needs larger N levels to respond, justifying the difference between them (FORNASIERE FILHO, 2007). Kappes and Silva (2016) obtained average increases of 7.6 % on grain yield with the N application, compared to the witness without N on side-dress, regardless the urea source used. Kappes et al (2009) observed significant increases in grain yield with the application of 70 kg ha -1 of N, regardless of the source used.…”
Section: Source: Elaborated By Authors (2019)mentioning
confidence: 80%
“…Já para a característica DE, as variedades BR 106, Caimbé e Porto Walter Tradicional apresentaram maior diâmetro, com médias 4,595 cm, 4,623 cm e 4,544 cm respectivamente. O CE é uma característica que apresenta alta herdabilidade, assim como o número de fileira por espiga (Tabela 2), enquanto que o DE pode apresentar variabilidade em função do ambiente e do manejo empregado (Brachtvogel, 2008;Fernandes et al, 2017;Kappes et al, 2009;Rizzardo, 2019).…”
Section: Resultsunclassified